Association of SARS-CoV-2 nucleocapsid viral antigen and the receptor for advanced glycation end products with development of severe disease in patients presenting to the emergency department with COVID-19 - Matthay, Zachary A.; Fields, Alexander T.; Wick, Katherine D.; Jones, Chayse; Lane, H. Clifford; Herrera, Kimberly; Nuñez-Garcia, Brenda; Gennatas, Efstathios; Hendrickson, Carolyn M.; Kornblith, Aaron E.; Matthay, Michael A.; Kornblith, Lucy Z.; et al. (Frontiers in Immunology, 2023)
There remains a need to better identify patients at highest risk for developing severe Coronavirus Disease 2019 (COVID-19) as additional waves of the pandemic continue to impact hospital systems. We sought to characterize the association of receptor for advanced glycation end products (RAGE), SARS-COV-2 nucleocapsid viral antigen, and a panel of thromboinflammatory biomarkers with severe disease in patients presenting to the emergency department with symptomatic COVID-19. Blood samples were collected on arrival from 77 patients with symptomatic COVID-19, and plasma levels of thromboinflammatory biomarkers measured. Differences in biomarkers between those who did and did not develop severe disease or death 7 days after presentation were analyzed. After adjustment for multiple comparisons, RAGE, SARS-COV-2 nucleocapsid viral antigen, interleukin (IL)-6, IL-10 and tumor necrosis factor receptor (TNFR)-1 were significantly elevated in the group who developed severe disease (all p<0.05). In a multivariable regression model, RAGE and SARS-COV-2 nucleocapsid viral antigen remained significant risk factors for development of severe disease (both p<0.05), and each had sensitivity and specificity >80% on cut-point analysis. Elevated RAGE and SARS-COV-2 nucleocapsid viral antigen on emergency department presentation are strongly associated with development of severe disease at 7 days. These findings are of clinical relevance for patient prognostication and triage as hospital systems continue to be overwhelmed. Further studies are warranted to determine the feasibility and utility of point-of-care measurements of these biomarkers in the emergency department setting to improve patient prognostication and triage.